Association of antibiotics with veteran visit satisfaction and antibiotic expectations for upper respiratory tract infections - Milner B. Staub; Rachael Pellegrino; Erin Gettler; Morgan C. Johnson; Christianne L. Roumie; Carlos G. Grijalva; Kaitlyn Reasoner; Robert S. Dittus; Todd Hulgan (Antimicrobial Stewardship & Healthcare Epidemiology, 2022)
Abstract